Guava Leaf Extracts Inhibit 3T3-L1 Adipocyte Differentiation Via Activating AMPK - Yoshitomi, Hisae; Qin, Lingling; Liu, Tonghua; Gao, Ming (Journal of Nutritional Therapeutics, 2013)
The guava tree (psidium guajava linn.) is commonly used not only as food but also as folk medicine. In our previous studies, we showed that oral administration of guava leaf extracts (GLE) had beneficial anti-obesity effects using metabolic syndrome model rats. However, we did not clarify molecular mechanism by which GLE administration leads to anti-obesity effect. This study was designed to evaluate the mechanism of anti-obesity by GLE using 3T3-L1 pre-adipocyte cell lines. We found that GLE significantly inhibited 3T3-L1 differentiation via down-regulation of adipogenic transcription factors and markers. Mitotic clonal expansion, which is essential for adipose differentiation, was also depressed in the early phase. Interestingly, GLE increased the phosphorylation of AMPK on 3T3-L1 cells and, by pretreatment with AMPK siRNA, the GLE treatment group showed restored adipocyte differentiation. In conclusion, these results showed that GLE is capable of inhibiting adipocyte differentiation via AMPK activation and therefore it may prevent obesity in vivo.